Budaya Literasi Melalui Peningkatan Minat Baca Masyarakat Adat di Kampung Ayapo Distrik Sentani Timur - Anwar, Rostini; K. Frank, Simon Abdi; Sriyono (UPT Perpustakaan UIN Alauddin Makassar, 2023)
High geographical conditions, a lack of educators and a lack of libraries which are one of the educational facilities in meeting the needs of indigenous Papuans, both from the general public to students, tend to be obstacles in encouraging literacy in Papua. Even students who cannot read well. Even though this reading skill is an asset for the indigenous Papuan people to be able to learn in order to realize superior Papuan human resources. Kampung Ayapo is a village on the shores of Lake Sentani, precisely in East Sentani District, Jayapura Regency. To get to Ayapo Village, it takes about 10 minutes by speed boat from Kalkote Beach. Until now, Ayapo Village has limited library facilities, although occasionally it is still visited by a mobile library with a type of floating library using a speed boat, so more effective and efficient methods are needed to achieve a literacy culture, one of which is by increasing indigenous people's interest in reading.